Periodismo y crítica de arte en las inauguraciones del primer centenario de la "Guerra de la Independencia" - Gómez Alfeo, María Victoria; García Rodríguez, Fernando (Historia y Comunicación Social, 2010)
Analysis of the information and art critic in the journalism from Madrid of 1908, on the inaugurated worksof art commemorating the "First Centennial of Guerra of the Independence. We detect an intent of regenera-cionismo of a nation without pulse, in expression of Silvela, after the defeat of the 98. It is about a "paideia",in Greek sense of educating in the "areté" or ideals of our culture.